Determining Functional Vitamin B12 Deficiency in the Elderly - Khodabandehloo, Niloofar (Iran Red Crescent Med J, 2015)
BACKGROUND: Elevated concentration of serum total homocysteine usually occurs in vitamin B-12 deficiency. This metabolite can be measured and used for screening functional vitamin B-12 deficiency. OBJECTIVES: We assessed functional vitamin B12 deficiency in Tehranian elderly admitted to elderly research center, University of Social Welfare and Rehabilitation Sciences. PATIENTS AND MATERIALS: A cross-sectional study was performed on 232 elderly admitted to elderly research center in Tehran, Iran in 2012. According to other studies, individuals were classified into two groups: high risk of vitamin B-12 deficiency (< 220 pmol/L) and borderline vitamin B-12 (220–258 pmol/L) accompanied by elevated homocysteine (> 15 micmol/L). RESULTS: Cut-off of 15.0 pmol/L for homocysteine was identified for persons with normal or elevated concentrations. Among persons aged 65–74 and ≥ 75 years, respectively, 56% and 93% were at high risk of vitamin B-12 deficiency. CONCLUSIONS: The prevalence of B12 deficiency was higher in this study compared to other studies, so more attention and massive efficacious policy should be designed to reduce the deficiency of this vitamin.